Effect of iron and magnesium addition on population dynamics and high value product of microalgae grown in anaerobic liquid digestate - Ermis, Hande; Guven-Gulhan, Unzile; Cakir, Tunahan; Altinbas, Mahmut (Springer Science and Business Media LLC, 2020)
AbstractIn this study, FeSO4 supplementation ranging from 0 to 4.5 mM, and MgSO4 supplementation ranging from 0 to 5.1 mM were investigated to observe the effect on the population dynamics, biochemical composition and fatty acid content of mixed microalgae grown in Anaerobic Liquid Digestate (ALD). Overall, 3.1 mM FeSO4 addition into ALD increased the total protein content 60% and led to highest biomass (1.56 g L−1) and chlorophyll-a amount (18.7 mg L−1) produced. Meanwhile, 0.4 mM MgSO4 addition increased the total carotenoid amount 2.2 folds and slightly increased the biomass amount. According to the microbial community analysis, Diphylleia rotans, Synechocystis PCC-6803 and Chlorella sorokiniana were identified as mostly detected species after confirmation with 4 different markers. The abundance of Chlorella sorokiniana and Synechocystis PCC-6803 increased almost 2 folds both in iron and magnesium addition. On the other hand, the dominancy of Diphylleia rotans was not affected by iron addition while drastically decreased (95%) with magnesium addition. This study helps to understand how the dynamics of symbiotic life changes if macro elements are added to the ALD and reveal that microalgae can adapt to adverse environmental conditions by fostering the diversity with a positive effect on high value product.
Keywords: Principal Component Analysis; Chlorophyll A; Algal Proteins; Fatty Acids; Synechocystis; Chlorella; Carotenoids; Ferric Compounds; Article; Up-Regulation; Magnesium Sulfate; RNA, Ribosomal, 16S; Microalgae; Biomass; Symbiosis